Bank Management : basic issues in money, bank lending & credit administration - Uremadu, Sebastian O. (Benin: Mindex Publishing Company, 2000)
The book is made up of eighteen chapters which include the following: bank deposit, a commercial bank's balance sheet, balance sheet item/ratios for evaluating bank performance, management of bank assets, bank liquidity management, profitability and liquidity of banks.
Includes bibliographical references
rua 20/07/16
Loans
Keywords: Bank Management; Money; Bank lending; Credit Administration